Early modern human lithic technology from Jerimalai, East Timor. Issue 101 (December 2016) - Marwick, Ben; Clarkson, Chris; O'Connor, Sue; Collins, Sophie
Abstract: Jerimalai is a rock shelter in East Timor with cultural remains dated to 42, 000 years ago, making it one of the oldest known sites of modern human activity in island Southeast Asia. It has special global significance for its record of early pelagic fishing and ancient shell fish hooks. It is also of regional significance for its early occupation and comparatively large assemblage of Pleistocene stone artefacts. Three major findings arise from our study of the stone artefacts. First, there is little change in lithic technology over the 42, 000 year sequence, with the most noticeable change being the addition of new artefact types and raw materials in the mid-Holocene. Second, the assemblage is dominated by small chert cores and implements rather than pebble tools and choppers, a pattern we argue pattern, we argue, that is common in island SE Asian sites as opposed to mainland SE Asian sites. Third, the Jerimalai assemblage bears a striking resemblance to the assemblage from Liang Bua, argued by the Liang Bua excavation team to be associated with Homo floresiensis . We argue that the near proximity of these two islands along the Indonesian island chain (c.100 km apart), the long antiquity of modern human occupation in the region (as documented at Jerimalai), and the strong resemblance of distinctive flake stone technologies seen at both sites, raises the intriguing possibility that both the Liang Bua and Jerimalai assemblages were created by modern humans.